The thermal and rewetting behavior of hot moving surface by water jet impingement. (August 2019) - Sharma, Avadhesh Kumar; Sahu, Santosh Kumar
Highlights: Thermal and rewetting behavior of hot moving surfaces with jet impingement are studied. The heat flux gradient in the axial direction decreases with plate motion. Local heat flux (except stagnation point) values are higher for moving surfaces. Rewetting velocity increases with the increase in plate velocity. Correlations are proposed for surface heat flux and rewetting velocity. Abstract: The present paper reports thermal and rewetting behavior of moving surfaces with upward circular water jet impingement. A stainless-steel foil (SS-304) with 0.15 mm thickness, used as a test specimen and temperature is measured by infrared thermal imaging camera, for transient cooling conditions. The initial surface temperature of the test foil is kept at 500 ± 10 °C, and the distance between nozzle to plate is maintained at 6. During tests, Reynolds number was varied between 2500 and 10000, while the plate test specimen speed was varied within 0 and 40 mm/s. Except for the stagnation zone (x = 0), the local heat flux values are found to be higher for moving surfaces compared to stationary surfaces. The heat flux gradient in the axial direction is higher for the stationary plate and reduces with increase in the plate speed. Nondimensional rewetting velocity is found to increase, with an increase in plate speed and Reynold Number.